Success Rate of Liver Stiffness Measurement Using Transient Elastography in Non-alcoholic Fatty Liver Disease Patients with Obesity and Its Influencing Factors - Edi Mulyana; Irsan Hasan; Marcellus Simadibrata; Hamzah Shatri (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Background: Percentage of patients who had liver stiffness measurement failure using transient elastography varied between 2-10%; mainly caused by obesity. XL probe is expected to increase the success rate of liver stiffness measurement in patients with obesity. The objective of this study is to evaluate the success of liver stiffness measurement using M and XL probes and its influencing factors.Method: Patients who fulfilled the inclusion criteria were included in this study. Examination results were then analysed using statistical analysis unpaired t-test or Mann-Whitney and McNemar statistical tests.Results: From 92 NAFLD patients with obesity who were studied, the proportion of success in measuring liver stiffness using M probe was 57.6%, while that of XL probe was 88.0%. This difference was statistically significant (p 0.001). BMI, SCD, and thoracic circumference were associated with success in measuring liver stiffness using M probe, with p value of 0.007, 0.001, and 0.001 respectively. The results of Mann-Whitney statistical test revealed median value of BMI and SCD of patients who had liver stiffness measurement failure using M probe were 32.7 kg/m2 and 2.6 cm respectively. T-test results showed that the mean value of thoracic circumference of patients who had liver stiffness measurement failure using M probe was 97.8 cm.Conclusion: Proportion of success in measuring liver stiffness in NAFLD patients with obesity using XL probe was better compared to the M probe. BMI, SCD, and thoracic circumference were associated with the success of measuring liver stiffness using M probe. The same variables were not associated with XL probe.